Introduction to mass communications - Agee, Warren Kendall (HarperCollins Publishers, 1991)
The twelfth edition of Introduction to Mass Communications accomplishes two goals essential for a mass communications textbook on the threshold of the twenty-first century. It plunges into the stimulating, still uncertain electronic realm of cyberspace. At the same time, it also examines traditional mass media with the depth and perception associated with previous editions. This text is user-friendly and replete with up-to-the-minute insights into contemporary mass communications practice. In a scholarly manner, Agee and Ault describe the historical evolution that has brought today's methods and ethical principles into being.